Gambaran Perilaku Sedentari Pada Siswa Sma X Kota Bekasi - Suci Nurul Aini; Lastriyanti Lastriyanti (JINTAN: Jurnal Ilmu Keperawatan, 2023)
Sedentary behavior is a daily activity outside of bedtime both night sleep and naps that do not require a lot of energy expenditure or low calorie expenditure. The purpose of this study was to see a description of sedentary behavior in SMA X Bekasi City. This research is a descriptive study with a quantitative approach. Primary data collection is obtained by direct retrieval through filling out the Global Physical Activity Questionnaire (GPAQ) questionnaire directly. Data processing using a computer system and data analysis using SPSS with Descriptive Statistics test. The results showed that there were students of SMA X Kota Bekasi who behaved sedentarily with a total of 56 students from a total of 77 students. The conclusion of this research is that many students of SMA X Kota Bekasi have sedentary behavior.